Loss of the ribosomal RNA methyltransferase NSUN5 impairs global protein synthesis and normal growth - Heissenberger, Clemens; Liendl, Lisa; Nagelreiter, Fabian; Gonskikh, Yulia; Yang, Guohuan; Stelzer, Elena M.; Krammer, Teresa L.; Micutkova, Lucia; Vogt, Stefan; Kreil, David P.; Sekot, Gerhard; Siena, Emilio; et al. (Nucleic acids research, 2019)
Abstract. Modifications of ribosomal RNA expand the nucleotide repertoire and thereby contribute to ribosome heterogeneity and translational regulation of gene